Thermal comfort in lecture halls in the tropics - Yau, Y.H.; Chew, B.T.; Saifullah, A. (2011)
A field study was conducted in six lecture halls DK1-DK6 of the Faculty of Engineering at University of Malaya, Kuala Lumpur to assess the thermal conditions during the lecture session. Comfort parameters were measured to analyze the acceptability of the thermal comfort simultaneously when 178 students answered a survey questionnaire on their thermal perception/sensation of the indoor climate. The measured data includes air temperature, mean radiant temperature, relative humidity, air velocity and personal variables. The response of the occupants in the lecture hall DK6 only is fulfilling the ASHRAE Standard 55, because PPD in this lecture hall is 5.8, whereas that in other lecture halls is above 10. Besides, AMV and PMV have been compared. Fanger’s model was used to calculate the neutral operative temperature (24.6°C), whereas the questionnaire data used in the TSV analysis gives higher value (25.3°C) for the neutral operative temperature. This is in good agreement with the neutral operative temperature (25.4°C) for Hong Kong. The humidity in the lecture halls DK1, DK4 and DK5 was below and that of the lecture halls DK2, DK3 and D6 was above the recommended range 50-60% RH. The air velocity in all the six lecture halls was below 0.2 m/s for normal room air distribution. The air velocity in the lecture hall DK6 was 0.08 m/s, which is too low. Metabolism in each hall was ≤ 1.2 met for light and primarily sedentary activity. The clo value in each lecture hall was above 0.55 clo for average people. Findings of this field study are useful in designing HVAC systems with energy savings for university lecture halls in the tropics.